Semantic analysis of Kayori speech in the traditional wedding ceremony of the pamona tribe - Treis Rumpajanji (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This research aimed at finding out the semantic meaning, particularly connotative meaning in kayori’s utterance in the traditional wedding ceremony of the Pamona tribe. This research was conducted in the village of Sangginora, Poso sub-district, the south coast of Poso district. This research is a qualitative research that uses data in the form of words, phrases, sentences and picture. Data collection techniques in this research are observation of the Pamona traditional wedding procession, interview with kayori’s speaker and field note. The theory used in this research to analyze the gained data is Semantic Meaning theory by Geoffrey Leech about Connotative meaning. The findings shows that 1) There are several words in a kayori that contain connotative meanings which than change a literal meaning of the kayori into a meaning that is in accordance with the content and purpose of kayori. 2) Kayori contains its own value in a traditional Pamona wedding ceremony because in the process of telling kayori it cannot be removed in every traditional wedding procession because kayori is one of the rules of wedding procedures in Pamona.